Perkembangan Balita Stunting Di Kota Kupang - Karmila, Yulia Martiningsih; Cicilia Saba, Chindy; Yashinta Goa, Maria (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Toddler development is an essensial aspect in children life. It is includes gross and fine motoric skill, personal and language developmental. Deviations of toddler development can be influenced by hereditary factors, prenatal, environmental, nutritional, hormonal, economic status and stunting incidence. Early detection of developmental delayed especially in stunted children is essensial in order to improve their optimal growth and delelopment in the future. The purpose of this study was to determined the development of stunted children in Kelurahan Alak, Kupang City. This research was a quantitative research with the type of descriptive research with cross-sectional approach. Sampling was done by purposive sampling technique and the number of samples in this study were 60 respondents. Data was collected by using Denver Development Screening Test II (DDST II) form. The results of this study indicate that the majority of stunted children in Kelurahan Alak Kota Kupang were in normal development (66,7%), where as minority of stunted children were in suspect development (33.3%). It is suggested that community health center officers can improve services regarding nutritional status and efforts to routinely detect early development of stunted children. As well as providing information not only regarding the growth but also development of children. Parents of stunted toddlers must continue to catch up with their child's weight and height delayed, while continuing to provide stimulation for optimal development of children during the golden age.